Principle and Architecture Analysis of VoWi-Fi Technology - Lei Cao; Bo Wang; Zhen Shao; Xiao Shen; Yiming Li (Dianxin kexue)
With the commercial application of VoWi-Fi technology and support of terminals such as apple mobile phone for Wi-Fi calling technology, VoWi-Fi technology has become a hot spot in the industry once again. The principle and architecture and key issues of the VoWi-Fi technology were introduced and analyzed, other VoWi-Fi technical implementation schemes were also studied. The problem of technology deployment of VoWi-Fi technology which merges with VoLTE which should be considered was put forward.